Integrating Local Wisdom in Ecopedagogy: Promoting Ecological Awareness in Society - Aulia Novemy Dhita; Edwin Nurdiansyah; Nana Supriatna; Didin Saripudin; Erlina Wiyanarti (Journal of Pedagogy and Education Science, 2026)
This study aims to examine efforts to foster ecological awareness among citizens through an ecopedagogical approach integrated with local community wisdom. The Bekarang tradition in South Sumatra is highlighted as an example of cultural practice that functions as a form of civic education beyond the boundaries of formal schooling. This tradition embodies values of environmental preservation, thereby contributing to the internalization of citizens’ rights and responsibilities, particularly concerning the natural environment. The research employs a qualitative approach with a conceptual paper design supported by a literature review. The literature serves as a basis for exploring, examining, and synthesizing key concepts. The findings indicate that ecopedagogy, when internalized through local traditions, can serve as an effective medium for transmitting ecological values to society. Environmental education grounded in local cultural values not only strengthens ecological identity but also encourages active citizen participation in environmental protection. This research underscores the importance of synergy between education, local wisdom, and policy in shaping environmentally conscious citizens who are actively involved in sustainability efforts.